A metallic glass syntactic foam with enhanced energy absorption performance. (1st July 2016) - Lin, H.; Wang, H.Y.; Lu, C.; Dai, L.H.
Abstract: By using the high-pressure melt infiltration technique, a syntactic foam is fabricated with bulk metallic glass and alumina cenospheres. Compared to pure metallic glass foams, the new foam possesses a greatly enhanced energy absorbing capacity of 113.6 MJ m − 3 due to the combination of high strength, stability and ductility. It is shown that the high strength of the foam primarily results from alumina cenospheres, which enhance its stability and induce a stable stress platform. Both the collapse of struts and multiple shear bands in metallic glass matrix accommodate large deformation. Graphical abstract: